Pengembangan Modul Fisika Berbasis Pembelajaran Kooperatif untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMA - Rifari Baron; Rosynanda Nur Fauziah; Sumarti Sumarti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Problem-solving ability is an important higher-order thinking competency in physics education. However, observations at SMAN 6 Tangerang indicate that students’ problem-solving ability remains low because learning is dominated by teacher-centered lectures and conventional textbooks that provide limited opportunities for active and collaborative learning. This study aimed to develop a cooperative learning-based physics teaching module to improve Grade X students’ problem-solving ability and to determine its validity, practicality, and effectiveness. The study employed a development research method using the Plomp model, consisting of the preliminary research, prototyping phase, and assessment phase. Data were collected through observations, interviews, questionnaires, documentation, and problem-solving tests based on Polya’s four stages, and were analyzed descriptively and statistically using IBM SPSS Statistics. The participants consisted of three heterogeneous Grade X classes, subject matter experts, and media experts. The results showed that the module was highly valid, with validation scores of 94.05% from subject matter experts and 97.50% from media experts. The module was also considered practical, while effectiveness testing involving 95 respondents yielded an average percentage of 82.17%, categorized as highly effective. Testing involving 102 students showed an increase in the mean score from 41.35 to 63.00, with an N-Gain of 0.407, categorized as moderate. The Wilcoxon Signed-Rank Test yielded a significance value of 0.000, indicating a significant difference between pre-test and post-test scores. Thus, the developed module is valid, practical, and effective in supporting students’ problem-solving ability.